A Critique of Western Buddhism Ruins of the Buddhist Real - Wallis, Glenn (Bloomsbury Academic, 2018)
What are we to make of Western Buddhism? Glenn Wallis argues that in aligning their tradition with the contemporary wellness industry, Western Buddhists evade the consequences of Buddhist thought. This book shows that with concepts such as vanishing, nihility, extinction, contingency, and no-self, Buddhism, like all potent systems of thought, articulates a notion of the "real." Raw, unflinching acceptance of this real is held by Buddhism to be at the very core of human "awakening." Yet these preeminent human truths are universally against contemporary Buddhist practice, contravening the very heart of Buddhism.